Impact of market orientation, organizational learning​ and market conditions on small and medium-size hospitality enterprises - Kasim, Azilah; Ekinci, Yuksel; Altinay, Levent; Hussain, Kashif (Routledge, 2018)
This paper focuses on the impact of Market Orientations (MO), Organizational Learning (OL) and Market Conditions (MCs) on Firm Growth (FG), within the context of hospitality Small and Medium Enterprises (SMEs) in Malaysia. Entrepreneurs/managers were sampled using cluster-sampling technique and surveyed using a 5-point Likert type scale instrument. The questionnaire’s validity was determined by 1) expert opinions, and 2) pilot testing the instrument on a small group of target respondents. A total of 254 completed questionnaires were analyzed to test the research model using Structural Equation Modeling approach (SEM) via the Partial Least Squares (PLS) software. The findings reveal that MO has a strong influence on FG and that OL partially mediates the MO-FG relationship. However, MCs have no moderating influence on the OL-FG relationship. The paper then discusses the findings’ implications on theory and practice.本文着重研究了马来西亚中小企业的市场定位、组织学习（OL）和市场条件（MCS）对企业成长的影响。企业家/管理者采用整群抽样方法，调查采用李克特仪器采样。问卷的有效性由1个专家意见决定，2）在一小群受试者身上进行测试。用偏最小二乘（PLS）软件对254份完成的问卷进行分析，用结构方程模型（SEM）对研究模型进行检验。研究结果发现，市场导向对企业成长有显著影响，组织学习部分中介市场导向-企业成长关系。然而，市场条件对组织学习,企业成长关系的影响不显著。然后讨论了这些发现对理论和实践的启示。